Clinical effectiveness of pharmacist-led versus conventionally delivered antiviral treatment for hepatitis C virus in patients receiving opioid substitution therapy: a pragmatic, cluster-randomised trial. (September 2020) - Radley, Andrew; de Bruin, Marijn; Inglis, Sarah K; Donnan, Peter T; Hapca, Adrian; Barclay, Stephen T; Fraser, Andrew; Dillon, John F
Summary: Background: Highly effective direct-acting antiviral drugs provide the opportunity to eliminate hepatitis C virus (HCV) infection, but established pathways can be ineffective. We aimed to examine whether a community pharmacy care pathway increased treatment uptake, treatment completion, and cure rates for people receiving opioid substitution therapy, compared with conventional care. Methods: This cluster-randomised trial was done in Scottish community pharmacies. Before participants were recruited, pharmacies were randomly assigned (1:1) to refer patients with evidence of HCV antibodies to conventional care or offered them care in the pharmacy (pharmacist-led care). Pharmacies were stratified by location. All pharmacies were trained to offer dried blood spot testing. All eligible participants had received opioid substitution therapy for approximately 3 months, and those eligible to receive treatment in the pharmacist-led care pathway were HCV PCR positive, were infected with HCV genotype 1 or 3, and were willing to have a pharmacist supervise their antiviral drug administration. Neither pharmacists nor patients were masked to treatment allocation. In both groups, assessment blood samples were taken, infection with HCV was confirmed, and daily oral ledipasvir–sofosbuvir (90 mg ledipasivir plus 400 mg sofosbuvir) for 8 weeks for genotype 1 or daily oral sofosbuvir (400 mg) plus oral daclatasvir (60 mg) for 12 weeks for genotype 3 was prescribed by a nurse (conventional care group) or pharmacist (pharmacist-led care group). In the conventional care group, the patient received care at a treatment centre. Once prescribed, medication in both groups was delivered as daily modified directly observed therapy alongside opioid substitution therapy in the participants' pharmacy where treatment was observed on 6 days per week. The primary outcome was the number of patients with sustained virological response 12 weeks after completion of treatment (SVR12) as a proportion of the number of people receiving opioid substitution therapy at participating pharmacies. Participants were monitored at each visit for nausea and fatigue; other adverse events were recorded as free text. Secondary outcomes compared key points on treatment pathway between the two groups. These key points were the proportion of patients having dry blood spot testing, the proportion of patients initiating HCV treatment, the proportion of patients completing the 8 or 12 week HCV course of treatment, and the proportion of patients with sustained virological response at 12 months. This study is registered with ClinicalTrials.gov, NCT02706223 . Findings: 56 pharmacies were randomly assigned (28 to each group; one pharmacy withdrew from the conventional care group). The 55 participating pharmacies included 2718 patients receiving opioid substitution therapy (1365 in the pharmacist-led care group and 1353 in the conventional care group). More patients met the primary endpoint of SVR12 in the pharmacist-led care group (98 [7%] of 1365) than in the conventional care group (43 [3%] of 1353; odds ratio 2·375, 95% CI 1·555–3·628, p<0·0001). More users of opioid substitution therapy in the pharmacist-led care group versus the conventional care group agreed to dry blood spot testing (245 [18%] of 1365 vs 145 [11%] of 1353, 2·292, 0·968–5·427, p=0·059); initiated treatment (112 [8%] of 1365 vs 61 [4%] of 1353, 1·889, 1·276–2·789, p=0·0015) and completed treatment (108 [8%] of 1365 vs 58 [4%] of 1353, 1·928, 1·321–2·813, p=0·0007). The data for sustained virological response at 12 months are not reported in this study: patients remain in follow-up for this outcome. No serious adverse events were recorded. Interpretation: Using pharmacists to deliver an HCV care pathway made testing and treatment more accessible for patients, improved engagement, and maintained high treatment success rates. The use of this pathway could be a key part of an integrated and effective approach to HCV elimination at a community level. Funding: Partnership between the Scottish Government, Gilead Sciences, and Bristol-Myers Squib.